Technical performance in the English Premier League - the influence of team quality and match location - Ma, S. (Journal of Human Sport & Exercise, 2025)
The purpose of this study was to compare the technical performance metrics of top- and bottom-tier English Premier League teams, examine the effect of match location on these metrics, and identify the statistically significant factors of winning. A total of 266 match observations were analysed via Mann-Whitney U tests and binary logistic regression. Top-tier teams had higher numbers in Shot, Shot on Target, Successful Take-On, Tackle Attacking 3rd, Pass Completed, Through Ball, Long Pass Completed, and Cross. Bottom-tier teams, on the other hand, recorded more Shot on Target Against, Clearance, Blocked Shot, Tackle Defensive 3rd, Yellow Card, Long Pass Completed %, and Aerial Duel Won. Generally, teams had increased offensive outputs in home games, while playing away primarily influenced defensive actions. For top-tier teams, each additional Aerial Duel Won and Shot on Target increased winning odds by 35% and 65%, respectively. Cross, Tackle Attacking 3rd, and Shot on Target Against decreased these odds by 30%, 43%, and 45%, respectively. Among bottom-tier teams, each event of Clearance increased odds of winning by 13%, while Shot on Target Against decreased them by 37%. These findings can be useful to coaches and performance analysts for evaluating and improving team performance.